(untitled) (Journal of Naval Architecture and Marine Engineering, 2011)
In the present study, an unsteady two-dimensional MHD free convection flow chemical reacting fluid past a semi-infinite permeable vertical moving plate in a porous medium with Soret and Dufour effects is analyzed. The dimensionless governing equations are solved numerically by a finite element method. Computations are performed for a wide range of the governing flow parameters, viz., the thermal Grashof number, solutal Grashof number, Magnetic field parameter, Permeability parameter, Prandtl number, Heat absorption parameter, Dufour number, Schmidt number, Chemical reaction parameter and Soret number. The effects of these flow parameters on the velocity, temperature and concentration are shown graphically. Finally, the effects of various parameters on the skin-friction coefficient, Nusselt number and Sherwood number are shown in Tables. DOI: http://dx.doi.org/10.3329/jname.v8i1.6054